Phase Composition Analysis Using Rietveld Methode and It's Influence To The Hardness Of Ti-Si-N Nanocomposites - Moto, Keba; Setiarini, Lia; Abubakar, Zufar (Makara Journal of Technology, 2003)
Phase composition analysis using rietveld methode and it’s influence to the hardness of Ti-Si-N nanocomposites. XRD data of nanocomposites Ti-Si-N have been analysed using GSAS based on Rietveld Method in order to identify phases and their composition as well as its influence on the hardness of these nanocomposites. Several new phases have been found in the sample beside the nc-TiN/a-Si3N4& a-/nc-TiSi2 that have been known widely. From the obtained crystalline phase, after the calculation of amorf Si3N4 and TiSi2 phase fraction, it is found that the optimum hardness can be reached when the fraction of a-Si3N4 phase around 8 wt.%